Profile of Candidiasis Patients in RSUD Dr. Moewardi Surakarta January 2016−December 2019 - Nurrachmat Mulianto; Siti Efrida Fiqnasyani (MEDICINUS, 2022)
Background: Candidiasis is caused by Candida sp. infection, mainly Candida albicans. The skin, mucous membranes, nails, and digestive tract are organs that can be affected by this infection. The risk of infection is higher in immunocompromised individuals. Objective: To determine the profile of candidiasis patients in Dr. Moewardi Hospital Surakarta between January 2016-December 2019. Method: This is a retrospective, descriptive study that evaluate the distribution of sex, age, primary diagnosis, comorbidities, and candidiasis type among candidiasis patients in RSUD Dr. Moewardi. Results: During study period, there were 177 candidiasis patients (147 outpatients and 30 inpatients). Pseudohyphae was seen in all inpatients’ KOH test. Majority of the patients are women (77,97%), age distribution varies between outpatients and inpatients. Cutaneous candidiasis was found in 53,74% outpatients and 66,67% inpatients. Type 2 diabetes mellitus was the most frequent (20%) comorbidity among those patients. Topical miconazole 2% and systemic fluconazole 150 mg were given to 42,37% and 33,90% patients, respectively.